2021
DOI: 10.2174/1570161118666200820141131
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Antiplatelet Therapies in Symptomatic Peripheral Artery Disease: A Systematic Review and Network Meta-Analysis

Abstract: Background: Clopidogrel monotherapy is guideline-recommended in symptomatic peripheral artery disease (PAD). The advent of new antithrombotic strategies prompts an updated analysis of available evidence on antiplatelet therapy for PAD. Methods: We searched MEDLINE, Embase and CENTRAL through January 2019 for randomised controlled trials and observational studies comparing antiplatelet therapies as monotherapy, dual therapy, or combination with anticoagulants. Efficacy (major adverse cardiovascular events, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…PTX3 is a more comprehensive inflammatory biomarker than traditional biomarkers, and it has links to renal fibrosis, cardiovascular disease, malnutrition, inflammation, and death prediction in HD patients. Targeting PTX3 may reduce the high morbidity and mortality rates associated with ESRD patients (25) , but clopidogrel should continue to be the backbone of treatment for PAD patients (26) .…”
Section: Discussionmentioning
confidence: 99%
“…PTX3 is a more comprehensive inflammatory biomarker than traditional biomarkers, and it has links to renal fibrosis, cardiovascular disease, malnutrition, inflammation, and death prediction in HD patients. Targeting PTX3 may reduce the high morbidity and mortality rates associated with ESRD patients (25) , but clopidogrel should continue to be the backbone of treatment for PAD patients (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Clopidogrel is a second-generation thienopyridine and a widely prescribed prodrug with anti-thrombotic activity through the irreversible inhibition of the P2Y receptor on platelets. Clopidogrel remains a mainstay of PAD treatment, with a significant reduction in MACEs in this population [117].…”
Section: Antiplateletsmentioning
confidence: 99%
“…It has been tested as an antiplatelet drug in clinical trials, resulting in approval as a platelet aggregation inhibitor in Italy 3–8 . Recent meta‐analyses have considered applications in prevention and prophylaxis of cardiovascular disease 9,10 . However, clinical and preclinical studies suggested that effects of picotamide are not limited to antiplatelet activity, or to inhibition of thromboxane A 2 ‐mediated functions.…”
Section: Introductionmentioning
confidence: 99%